PREFERENSI, POLA KONSUMSI DAN KEPUASAN KONSUMEN SANTAN INSTAN DI PASAR MODERN KOTA BANDAR LAMPUNG - Kania, Nizka; Prasmatiwi, Fembriarti Erry; Marlina, Lina (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2025)
The purpose of this research is to analyze preferences, consumption patterns, and consumer satisfaction in purchasing instant coconut milk at modern market of Bandar Lampung City. The research method was a survey with the accidental sampling approach to select 60 respondents at Chandra Superstore and Chamart Gajah Mada located in Tanjung Karang Timur sub-district, Super Indo and Indomaret Kemiling at Kemiling sub-district. Data collection was carried ou  in February 2025. The analytical methods used were conjoint analysis, quantitative descriptive analysis, Customer Satisfaction Index (CSI), and Importance Performance Analysis (IPA). The findings indicate that the consumers of instant coconut milk in the range of age between 35-40 and 41-46 years old   have the same percentage, which is 26.67 percent. The attributes of instant coconut milk that became consumer preferences are Instant coconut milk with a sharp and distinctive aroma, in the package of 65 ml, have an expiration date more that 3 months, and the composition consists of more than 85 percent coconut milk. Meanwhile, the brand that coconut milk instant that often purchase by the consumers are Sasa and Kara (21 respondents or 35 percent) in the last month there were 29 respondents who consumed 65 ml instant coconut milk.  The average purchase and consumption is 130.08 ml/transaction with an average frequency of 2.4 times/month in the last month.  There are 83.33 percent consumers who use instant coconut milk as a complement to savory cooking ingredients.  Consumer satisfaction reaches 75.40 percent which falls into satisfied in category. The attributes that require immediate improvement are aroma, nutritional value, and price.   Key words:   consumption pattern, customer satisfaction, instant coconut milk, preference